Cognitive Performance in Older Adults Is Inversely Associated with Fish Consumption but Not Erythrocyte Membrane n–3 Fatty Acids. Issue 3 (18th December 2013) - Danthiir, Vanessa; Hosking, Diane; Burns, Nicholas R.; Wilson, Carlene; Nettelbeck, Ted; Calvaresi, Eva; Clifton, Peter; Wittert, Gary A.
Abstract: Higher n–3 (ω-3) polyunsaturated fatty acids (PUFAs) and fish intake may help maintain cognitive function in older age. However, evidence is inconsistent; few studies have examined the relation in cognitively healthy individuals across numerous cognitive domains, and none to our knowledge have considered lifetime fish intake. We examined associations between multiple domains of cognition and erythrocyte membrane n–3 PUFA proportions and historical and contemporary fish intake in 390 normal older adults, analyzing baseline data from the Older People, Omega-3, and Cognitive Health trial. We measured n–3 PUFA in erythrocyte membranes, and we assessed historical and contemporary fish intake by food-frequency questionnaires. We assessed cognitive performance on reasoning, working memory, short-term memory, retrieval fluency, perceptual speed, simple/choice reaction time, speed of memory-scanning, reasoning speed, inhibition, and psychomotor speed. Cognitive outcomes for each construct were factor scores from confirmatory factor analysis. Multiple linear regression models controlled for a number of potential confounding factors, including age, education, sex, apolipoprotein E-ɛ 4 allele, physical activity, smoking, alcohol intake, socioeconomic variables, and other health-related variables. Higher erythrocyte membrane eicosapaentonoic acid proportions predicted slower perceptual and reasoning speed in females, which was attenuated once current fish intake was controlled. No other associations were present between n–3 PUFA proportions and cognitive performance. Higher current fish consumption predicted worse performance on several cognitive speed constructs. Greater fish consumption in childhood predicted slower perceptual speed and simple/choice reaction time. We found no evidence to support the hypothesis that higher proportions of long-chain n–3 fatty acids or fish intake benefits cognitive performance in normal older adults.